46.6k views
2 votes
15 - 2(3 - 2x) = 46

User Numerlor
by
5.6k points

2 Answers

4 votes
-2(3-2x) = 46-15
-2 (3-2x) = 31
3-2 = -31/2
-2x = -31/2 - 3
-2x = -37/2
X = 37/2/2
X = 37/2 x 2
X= 37/4
User Sawel
by
5.3k points
1 vote

Answer:

x=33

Step-by-step

subtract 15 and 2 you get 13

13 times 3 =39

subtract 39 with 39 and 46 with 39

at the end you will get -26x=7

reverse negative into positive and then add -26 with 26 and you will be left with x and then you add 7 with 26 and your answer is

x=33

User Maroxe
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.